Stretched Earlobe Piercings Negatively Impact Casual Observer Perceptions - Fung, Nicholas; Ishii, Masaru; Huynh, Pauline; Juarez, Michelle; Bater, Kristin; Darrach, Halley; Papel, Ira D.; Kontis, Theda; Nellis, Jason C.; Ishii, Lisa (Facial Plastic Surgery, 2019)
Patients with stretched earlobes seek reconstruction to mitigate social stigma. To date, there have been no studies measuring the impact of stretched earlobe piercings on casual observer perceptions. One-hundred seventy-three casual observers were enrolled via public-access web sites. Participants were randomly shown frontal and profile views of six subjects with stretched earlobe piercings and four controls. Participants evaluated photos for first impressions using a survey containing choices regarding personal attributes. Latent class analysis was performed to categorize observer ratings. Analysis of variance (ANOVA), bootstrap analysis, and permutations testing were used to evaluate the relationship between perceived attractiveness, success, and approachability scoring and stretched earlobe status. Latent class analysis categorized responses into three classes: positive, negative, and neutral. Patients with stretched earlobe piercings were significantly less likely to be classified as positive by observers without body modifications (i.e., tattoos and piercings) in comparison to control photos (30.9 and 40.1%, p = 0.007) and more likely to be classified as negative (38.5 and 28.1%, p = 0.002). These changes were abolished when photos were evaluated by observers with body modifications (p > 0.05). ANOVA revealed that stretched earlobe piercings and observer body modification status have a significant effect on rated approachability (F [1,1726] = 4.08, p = 0.04) and successfulness (F[1,1726] = 9.67, p = 0.002; F [1,1726] = 70.33, p < 0.0005). No significance was found for rated attractiveness (p > 0.05). Patients with stretched earlobe piercings were more likely to be classified as having negative affect display and being less approachable and successful compared with controls when evaluated by observers without body modifications. This effect was abolished when photos were evaluated by observers with body modifications. These findings validate patient motivations for seeking stretched earlobe repair.
Keywords: stretched earlobe piercings; gauge piercings; homophily; social perception; reconstruction motivation